Wasting condition as a marker for severe disease in pediatric Crohn's disease. Issue 20 (20th May 2022) - Jin, Wook; Yang, Dong-Hwa; Tchah, Hann; Kwon, Kwang-An; Kim, Jung-Ho; Jeong, Su-Jin; Hahm, Ki-Baik
Abstract : Abstract: Several studies have shown an association between sarcopenia and clinical outcomes in patients with Crohn's disease (CD). However, studies have shown different results, and the association between prognosis and wasting conditions in pediatric patients with CD is uncertain. In this study, we evaluated the clinical significance of wasting in pediatric CD patients. We retrospectively analyzed data on wasting syndrome in patients diagnosed with CD at the Pediatric Department of Gachon University Gil Medical Center between January 1995 and January 2018. Of 105 patients diagnosed with CD, 39.0% were classified into the wasting group (weight-for-age z-score ≤−1) and 61.0% into the nonwasting group (weight-for-age z-score >−1). Height-for-age and body mass index-for-age z-scores at the time of diagnosis were significantly associated with wasting ( P  < .001 and P  < .001, respectively). Additionally, wasting was significantly associated with low levels of hemoglobin ( P  < .001), high levels of inflammatory markers, including C-reactive protein ( P  = .005) and erythrocyte sedimentation rate ( P  = .04), and a smaller surface area of the gluteus maximus muscle ( P  < .001). Interestingly, since the site of CD involvement and other markers for nutrition did not correlate with wasting syndrome, wasting appears to be a marker for the severity of pediatric CD. Lastly, the wasting group tended to have a greater use of biologic therapy after first-line therapy failed to improve wasting syndrome. Wasting syndrome, including sarcopenia, can serve as a marker for the severity of pediatric CD.